A case report of palliative care for a critically ill COVID-19 patient based on the Cordon assessment model (基于Cordon评估模式下1例COVID-19重症患者的安宁疗护) - LIU Yunxia (刘云霞); WANG Yunyan (王云艳) (中西医结合护理, 2023)
To summarize the nursing experience of a patient with severe COVID-19 under the Cordon assessment model. Assessment was carried out using the Cordon health pattern model. Based on the method of nursing procedure and concept of narrative nursing, nurses had determined nursing problems and set nursing goals and nursing measures. Comprehensive nursing management was carried out through multidisciplinary team cooperation. Traditional Chinese Medicine nursing technology was used to relieve the discomfort of terminally ill patients, provide them with physical, mental, spiritual and other aspects of care and humanistic care, and help patient to pass away comfortably, peacefully and with dignity. (总结基于Cordon评估模式下1例COVID-19重症患者安宁疗护经验。护理要点包括: 应用Cordon健康型态模式进行评估; 通过护理程序的方法和叙事护士的理念, 确定护理问题, 制定护理目标与护理措施; 通过多学科团队合作, 提供全程全面管理; 整个照护过程中以终末期患者和家属为中心, 运用中医护理技术, 缓解临终患者的不适, 提供身、心、灵等方面的照料和人文关怀, 帮助患者舒适、安详、有尊严的离世。)